IMPLEMENTASI PROGRAM JUM’AT ISLAMI DALAM MENANAMKAN NILAI KEJUJURAN PADA SISWA SMPN 3 MARON - M Mahbubi; Zahrani Yulia Agustin; RANI, ZAHRANI YULIA AGUSTIN (LPPM STAI Muhammadiyah Probolinggo, 2026)
The decline in honesty values among students manifested through behaviors such as cheating, lying, and irresponsibility poses a significant challenge to both the quality of education and the moral development of young people. This calls for systematic and sustainable efforts by educational institutions, especially through religion-based character education. This study aims to analyze the implementation of the Islamic Friday Program and its effectiveness in instilling the values of honesty among students at SMPN 3 Maron. This research uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation, analyzed via source triangulation to ensure validity. The implementation of the Islamic Friday Program is regular and systematic, involving activities such as congregational Dhuha prayers, Qur'an recitation, brief religious lectures, Asmaul Husna recitation, and collective prayers, all engaging the entire school community. The program has a positive impact on developing students’ honesty, reflected in increased spiritual awareness, a noticeable reduction in academic dishonesty violations, and growing courage among students to admit mistakes. Additionally, it fosters a religious school culture that promotes discipline, responsibility, and exemplary behavior. These findings suggest that consistent religious activities effectively internalize honesty values both emotionally and spiritually, making the Islamic Friday Program a strong model for character education in schools.